PERFORMANCE ANALYSIS OF RECUPERATOR OF RGTT200K CONCEPTUAL DESIGN USING CHEMCAD - Piping Supriyatna; Sriyono Sriyono (Badan Tenaga Nuklir Nasional, 2015)
RGTT200K is a high temperature gas cooled reactor with 200 MW thermal powers, designed with cogeneration concept to produce hydrogen, electricity generation and potable water by desalination process. RGTT200K uses helium gas as a coolant with core inlet tem-perature of 615 °C and outlet temperature about 950 °C. The coolant is circulated at 120 kg/sec mass flow rate at initial pressure of 5 MPa. To keep material integrity of RGTT200K structure, the recu-perator performance of RGTT200K must be maintained due to its double function. Those main func-tions are to reduce the output temperature coolant from the turbine and transfer it back to the main primary circuit using a compressor and to increase the coolant gas from the compressor before ente-ring the core again. This paper describes an analysis to evaluate the recuperator performance by mo-delling using ChemCAD computer code. The calculation results showed that to obtain the core inlet temperature of 615 °C with the recuperator effectiveness of 0.95, the value of the logarithmic mean temperature difference (LMTD) should be 2.51, and the recuperator heat load (BPR) of 264.7 and the heat exchanger coefficient and heat exchange (UA) of 10.546 are needed. Based on those values, the difference between the inlet and outlet temperature of reactor core is not so big and still in stable con-dition to maintain the material structure integrity of the core.